Are mind-body therapies beneficial for older people with dementia? A Systematic Review and meta-analysis of randomized controlled trials - Mei, Zhengyang; Cai, Chenyi; Wang, Tingfeng; Zhang, Yuanzhuo; Zhao, Wen; Lam, Chifong; Luo, Shulai; Shi, Yu; Luo, Shi (Frontiers in Psychiatry, 2025)
ObjectiveThis systematic review and meta-analysis aimed to evaluate the potential multidomain benefits of mind-body therapies (MBTs) for behavioral and psychological symptoms of dementia (BPSD) in older people with dementia (OPWD).MethodsRelevant randomized controlled trials (RCTs) were identified using electronic databases and manual searches. Two independent researchers evaluated the risk of bias in the included trials using the Revised Cochrane Risk-of-Bias tool for randomized trials. A standardized mean difference (SMD) with a 95% confidence interval (CI) was used to combine effect sizes.ResultsThis review included 35 RCTs comprising 4,043 patients, of whom 24 were included in the meta-analyses. MBTs effectively improved BPSD (SMD = -0.33; 95% CI -0.49 to -0.16; p < 0.01), anxiety (SMD = -0.82; 95% CI -1.53 to -0.10; p = 0.02), and depression (SMD = -0.57; 95% CI -1.06 to -0.08; p = 0.02), with no significant improvements observed in agitation (SMD = -0.09; 95% CI -0.25 to 0.07; p = 0.27) among patients with dementia. The certainty of evidence across the outcomes ranged from low to very low, based on the Grading of Recommendations, Assessment, Development, and Evaluations ratings.ConclusionEffective nursing for patients with dementia is vital, as they are undergoing a major transition in their physical and mental health. In clinical practice, healthcare and social care therapists should develop personalized intervention programs based on patient individual differences and the actual dose-response relationship, which will help maximize the clinical benefits of non-pharmacological treatments in the context of limited medical resources. More high-quality RCTs could be conducted to compare the differential efficacy of non-pharmacological treatments on various aspects of BPSD in OPWD to provide a better evidence base to guide individual care and policy guidance.Systematic review registrationPROSPERO, identifier CRD42024559809.